Raspberry like creosol red functionalized zincite supported silica-titania nanocomposite: Correlation of structural, optical, and pH sensing properties. (November 2022) - Islam, Shumaila; Alshoaibi, Adil
Highlights: Owing to fast-response and broad pH range, sol-gel based cresol red encapsulated zincite supported silica-titania nanocomposite is synthesized at low- temperature. CR/ZSTC had raspberry-like porous structure with uniform distribution of elements. The CR/ZSTC exposed ra ∼ 6 nm, transmission 86%, and n around 1.49 at 633 nm. A fast color time response of 0.5 s at pH 12 and high pKa value around 8 is detected. Experimental findings suggested that synthesized CR/ZSTC has potential for optical pH sensor. Abstract: Owing to fast-response and broad pH range, sol-gel-based zincite (zinc oxide) supported silica-titania nanocomposite (ZSTC) and cresol red encapsulated ZSTC (CR/ZSTC) are synthesized at low- temperature. SEM and EDX mapping exhibited that CR/ZSTC had a raspberry-like porous structure with uniform distribution of elements. The ZSTC exhibited a Ra (surface roughness) 1 nm, transmission 87%, and a refractive index (n) 1.48. The CR/ZSTC exposed Ra ∼ 6 nm, transmission 86%, and n around 1.49 at 633 nm. A fast color time response of 0.5 s at pH 12 and a high pKa value around 8 is detected. Experimental findings suggested that synthesized CR/ZSTC has the potential for optical pH sensors. Graphical abstract: Image, graphical abstract